Normative Reference Values for Handgrip Strength in Chilean Children at 8-12 Years Old Using the Empirical Distribution and the Lambda, Mu, and Sigma Statistical Methods - Vegas-Heredia, E; Fernandez-Vergara, O; Cofre-Bolados, C; Garcia-Hermoso, A; Andrade-Schnettler, R (NSCA National Strength and Conditioning Association, 2021)
The aim of this study was 2-fold (a) to provide sex- and age-specific handgrip reference standards for Chilean children aged 8-12 years and (b) to compare the levels of handgrip strength of Chilean children with those of children from other countries. This cross-sectional study enrolled 2,026 schoolchildren (boys n = 1,334 and girls n = 692, mean age 10.18 [1.16] years old). Handgrip strength was measured using a hand dynamometer with an adjustable grip. Relative handgrip strength was calculated by dividing handgrip strength by body mass (handgrip strength kg per mass kg). Smoothed centile curves and tables for the 10th, 20th, 30th, 40th, 50th, 60th, 70th, 80th, and 90th centiles were calculated using Cole s lambda, mu, and sigma method. The results indicate that mean handgrip strength was greater among boys than girls. Handgrip strength peaked at 16.25 (5.03) kg in boys and 14.90 (4.32) kg in girls. In addition, relative handgrip strength peaked at 0.38 (0.08) in boys and 0.34 (0.07) in girls. Chilean children of both sexes scored higher than their South American counterparts from Colombia and Peru but showed lower handgrip strength than European and Australian children. Our results provide, for the first time, sex- and age-specific handgrip reference standards for Chilean children aged 8-12.9 years. These normative reference values could help identify the levels of handgrip strength that need attention to provide appropriate feedback and advice to children about how to best improve their overall physical fitness. © 2021 NSCA National Strength and Conditioning Association. All rights reserved.